Partisipasi Perempuan dalam Pembangunan Pendidikan di Desa Belawan Mulya Kecamatan Manuhing Kabupaten Gunung Mas: Women's participation in the development of education in the village of Belawan Mulya Manuhing District Gunung Mas District - Ratmoko, Ambar; Marifah, Siti Fadillatul (Pencerah Publik, 2015)
Basically, the research aims to know how to form the participation of women in the development of education in the village Belawan Mulya Manuhing District of Gunung Mas District, and what are the obstacles of women in participating. The study uses qualitative descriptive research methods, data collection techniques using interviews, observations and documentation, interviews to women. The data analysis techniques used are data collection, data reduction, data feeds and drawing conclusions/verifications. The results of this research are the development of education in the village Belawan Mulya not go well, educational facilities are not yet complete and form of women's participation in the development of education in this village in the form of energy, money, and expertise. While the inhibitory factor of female participation in this village is, age, the background of education is still low, the economic level of the population is still low and lack of support facilities of their participation such as lack of educational facilities. Based on the results of this study, women should continually improve their self-esteem in order to perform many roles, especially roles in education, in addition to women together with governments, social organizations and communities in order to cooperate to build educational facilities